008. Massive Teratoma Attached to The Inferior Vena Cava and Abdominal Aorta in Pediatric Patient: A Case Report - Natario, Natario; Darmajaya, I Made (JBN (Jurnal Bedah Nasional), 2024)
Background : Massive teratomas are rare and complex tumors that can grow large and involve crucial structures, such as the inferior vena cava (IVC) and abdominal aorta. These tumors can be challenging to resect, especially in pediatric cases, due to their size and proximity to vital organs. Case : A 9-year-old boy was admitted with a history of an abdominal mass first detected at age 3. Over the years, the mass had progressively enlarged, initially the size of a grape and later the size of a tennis ball by age 6. Recent imaging, including CT scans, showed a retroperitoneal mass measuring approximately 20 x 10 cm with characteristics of a mature cystic teratoma. The mass was compressing surrounding structures, including the duodenum, pancreas, and left kidney, and was adherent to both the IVC and abdominal aorta. The surgical team performed a laparotomy with adhesiolysis, extensive tumor excision, and vascular repair. Vascular control was established, and the tumor was successfully removed, including sheared portions of the abdominal aorta, which required ligation and repair of the affected vessels. Conclusion: This case illustrates the complexity and challenges of managing massive retroperitoneal teratomas. Through a multidisciplinary approach, it was possible to achieve complete excision and ensure the patient’s recovery with no immediate complications.